2004
DOI: 10.1007/s00421-003-0970-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term creatine supplementation does not improve muscle activation or sprint performance in humans

Abstract: The purpose of this study was to examine the influence of short-term creatine (Cr) supplementation on exercise-induced transverse relaxation time (T2) and sprint performance during maximum intermittent cycling exercise using the muscle functional magnetic resonance imaging (mfMRI) technique. Twelve men were divided into a Cr supplementation group [the Cr group, taking 4 x (5 g Cr monohydrate + 2.5 g maltodextrin)/day], or a placebo supplementation group (the P group, taking 4 x 7.5 g maltodextrin/day). The all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 44 publications
2
18
3
2
Order By: Relevance
“…The volume of the AD muscle group showed no significant difference between the operated and non-operated limb. Although the real function of the AD muscle during movement, including that in daily life, is not well known, recent studies have revealed that this muscle group is involved in basic human movements such as running and cycling [2,13,15,17]. We showed that this muscle group did not decrease in volume, thus the effect of the AD on these movements would be less after the surgery.…”
Section: Discussionmentioning
confidence: 69%
“…The volume of the AD muscle group showed no significant difference between the operated and non-operated limb. Although the real function of the AD muscle during movement, including that in daily life, is not well known, recent studies have revealed that this muscle group is involved in basic human movements such as running and cycling [2,13,15,17]. We showed that this muscle group did not decrease in volume, thus the effect of the AD on these movements would be less after the surgery.…”
Section: Discussionmentioning
confidence: 69%
“…For example, it offers the opportunity to investigate all the muscles engaged in the external work rather than those regions proximal to surface electrodes and allows spatial mapping of muscle "activity" during exercise. In the present study, we used this property to investigate activity patterns (2,4,18,25,33) in a cross section of 10 leg muscles during cycle ergometry over a range of intensities.…”
Section: Discussionmentioning
confidence: 99%
“…AU = arbitrary units. Kinugasa et al (2004) and Racinais et al (2007). Therefore, of the muscles analyzed, it is possible the reduction of ambulatory movement in pigs fed a RAC diet may be due to a reduction in muscle fiber recruitment in the ST, a muscle that is important in extending the hip, stifle, and hock and flexes the stifle when the leg is lifted .…”
Section: Electromyographymentioning
confidence: 99%